2009
DOI: 10.1248/jhs.55.657
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of the Interleukin-1 beta (IL-1.BETA.) -511 and +3954 Single Nucleotide Polymorphisms (SNPs) in Malaysian Systemic Lupus Erythematosus (SLE) Patients

Abstract: Systemic lupus erythematosus (SLE)is an autoimmune disorder whereby the immune system's components act upon our body's self-antigens. The pathogenesis is mainly due to the hyperactivity of T helper cells and B lymphocytes, as well as an abnormal apoptosis pathway. SLE has been linked to several genes, including the interleukin-1 beta (IL-1β), as it is primarily involved in the stimulation of B cells proliferation and differentiation, as well as costimulation of T cell activation, together with activation of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Similar statistical analysis as reported previously has been carried in this study (Chua et al, 2009b). The distribution of genetic polymorphisms was obtained by calculating both allelic and genotypic frequencies.…”
Section: Discussionsupporting
confidence: 54%
“…Similar statistical analysis as reported previously has been carried in this study (Chua et al, 2009b). The distribution of genetic polymorphisms was obtained by calculating both allelic and genotypic frequencies.…”
Section: Discussionsupporting
confidence: 54%
“…Others studies have also shown the predominance of the ancestral allele (C), ranging from 60% to 70%. [27][28][29] We observed a higher frequency of CC genotype (51.0%), followed by CT (31.8%) and TT (17.2%). This is consistent with the previously cited studies.…”
Section: Discussionmentioning
confidence: 59%
“…This is consistent with the previously cited studies. [27][28][29] Pro-inflammatory cytokines are produced in various organ after tissue damage not only in experimental immune-response models but also in various types of insults, including infection, ischemia, trauma, cryo-ablation and burns, [12] by various types of cells, including residential immune-related cells (such as leukocytes, macrophages, microglia, and dendritic cells), neurons and glia in the central nervous system. [25] As disruption of the blood-labyrinth barrier is associated with increased permeability of blood vessels in the inner ear, inflammation may be related to the etiology of these inner ear diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, no association between IL-1 β −511 C/T polymorphism and SLE was observed [53]. In a similar study carried out by Chua and coworkers [27], a significant correlation of another IL-1 β polymorphism (+3954 E1/E2 in exon 5) with SLE susceptibility in Malaysian population was noted, with E1 allele rather than the E2 at higher frequency among patients. This was also the case in Columbian SLE patients but not in the Taiwanese [53, 54].…”
Section: Candidate Genesmentioning
confidence: 99%